The study thyme of varieties (Thymus and Satureja) from the collection of the Institute of Genetics, Physiology and Plant Protection of Moldova State University - Lilia Chisnicean; Zinaida Vornicu; Tamara Jelezneac (Acta et Commentationes Exact and Natural Sciences, 2025)
Over the course of several years, within the collection of the Institute of Genetics, Physiology and Plant Protection of Moldova State University (IGPPP of MSU), various thyme varieties from the genera Thymus and Satureja, which have a special place among aromatic and culinary species, have been studied and tested. This paper presents an analysis of the results obtained from open field testing of four thyme varieties belonging to the Satureja and Thymus genera. The following important characteristics for these species were elucidated: quantitative morphometric parameters, raw material yield, pharmaceutical herb production, essential oil output per hectare, seminological indices, and propagation methods. The dissemination of these results led to the development of the new two varieties: Satureja montana L. ‘Alfa-14’ and Thymus × citriodorus – ‘Lyli-roz’, which have been submitted, registered and patented by the authorized bodies in the Republic of Moldova.